Comparative characteristics of various methods of osteosynthesis in wounded subjects with gunshot lesions of long bones - P.V. Tanasiienko; V.V. Vasylov (Bolʹ, Sustavy, Pozvonočnik)
Background. In the structure of combat injuries, gunshot wounds of the limbs prevail, which make up 50–80 % of all wounds, of which 57.3 % have multiple injuries of the limbs. At least one-quarter of all combat injuries involve the lower extremities. The purpose was to compare and choose the optimal osteosynthesis system to improve the provision of medical care to wounded people with gunshot injuries of long bones. Materials and methods. To fulfill the objectives of our study, we analyzed 174 cases of long bone injuries received as a result of modern warfare during the full-scale invasion of russia in the period from 2022 to 2024. Two comparison groups were formed in the study. The first group included 93 patients who underwent consecutive osteosynthesis, which accounted for 53.4 % of the total array. The second group included 81 patients with one-stage transosseous external osteosynthesis, which accounted for 46.6 % of the total array. Results. Among patients with conversion osteosynthesis, the complete union was observed in 73.1 %, which is 11.5 % more than when using one-moment osteosynthesis. Among the wounded with conversion osteosynthesis, delayed consolidation of fractures was observed in 11.8 %, while this indicator was 17.3 % when single-moment osteosynthesis was used. In patients with conversion osteosynthesis, osteomyelitis was detected less often, observed in 25.8 % of cases. Wound suppuration and implant instability were detected in 14.5 % of patients. Conclusions. The use of the technique of two-stage conversion osteosynthesis in injured patients with isolated gunshot fractures of the long bones of the limbs ensures better anatomical and functional results in comparison with the technique of transosseous one-moment osteosynthesis. When using the conversion method of osteosynthesis, the number of infectious postoperative complications, particularly the development of osteomyelitis and wound suppuration, significantly decreased. The data of our study testify to the priority use of the conversion method of osteosynthesis in patients with gunshot wounds of long bones.